Strengthening Character and Social Awareness among Adolescents through Literacy and Environmental Education Programs around SMK Ki Hajar Dewantoro - Lina Sukanti; Aniek Widiarti (The International Journal of Education Management and Sociology, 2025)
This study aims to describe the efforts to strengthen character and social awareness among adolescents through literacy and environmental education programs at SMK Dewantoro. The research background is based on the importance of cultivating environmental and social awareness in the younger generation as essential capital for facing global challenges and ensuring environmental sustainability. This study employed a qualitative descriptive method with data collected through observation, interviews, and documentation. The literacy and environmental education program was implemented through activities such as reading and discussing environmental literature, school clean-up actions, waste management, tree planting, and energy-saving campaigns. The results indicate that the program successfully fostered students’ awareness of the importance of cleanliness, ecosystem preservation, empathy, and social care within both the school and the surrounding community. Furthermore, students showed improvements in discipline, responsibility, cooperation, and a sense of belonging toward the environment. These findings confirm that integrating literacy and environmental education into school activities effectively shapes students’ social and environmental awareness and can serve as a model for other schools in promoting sustainable education.